Masalah Keluarga dalam Novel Puspita Rinengga Karya Tulus Setiyadi (Kajian Sosiologi Sastra) - Rahmawati, Illa; Darni, Darni (Jurnal Online Baradha, 2023)
Abstract Family problems are common problems in household life, but not all family problems can be solved. The existence of family problems can lead to acts of violence as a result of these problems. Puspita Rinnengga is one of Tulus Setiyadi's literary novels, which describes the family problems that occur among the characters. The aims of this study are (1) to explain deviant acts and (2) to explain the acts of violence experienced by the characters in Puspita Rinengga's novel. This research will be studied using Wellek and Warren's study of the sociology of literature, which focuses on the sociology of the content of literary works and examines the social elements and problems in literary works. This study uses qualitative research. The data source in this study is the novel Puspita Rinengga. This research data uses words, sentences, and conversations related to deviant acts and acts of violence. The techniques used to collect data in this study included library techniques, reading techniques, note-taking techniques, and data grouping techniques. Data analysis techniques in this study were divided into four categories: data preparation and organization, data reduction, data presentation, and conclusions. The results and discussion of this study are: (1) deviant acts whose forms are bisexual, becoming effeminate, and prostituting (2) acts of violence whose forms are neglected and prohibited from being independent and which cause misery and economic dependence Keywords: Deviant action, Abandoned, prohibited, Independent Abstrak Masalah keluarga merupakan masalah yang lumrah terjadi dalam kehidupan rumah tangga, akan tetapi tidak semua permasalahan keluarga dapat diselesaikan. Adanya permasalahan keluarga dapat menyebabkan tindak kekerasan sebagai akibat dari permasalahan tersebut. Novel Puspita Rinengga merupakan salah satu novel karya sastra Tulus Setiyadi yang menggambarkan masalah keluarga yang terjadi diantara para tokoh. Tujuan penelitian ini yaitu (1) Menjelaskan tindakan menyimpang (2) Menjelaskan tindak kekerasan yang dialami oleh tokoh dalam novel Puspita Rinengga. Penelitian ini aka dikaji menggunakan kajian sosiologi sastra Wellek dan Warren yang berfokus pada sosiologi isi karya sastra yang mengkaji unsur dan masalah yang berkaitan dengan sosial pada karya sastra. penelitian ini menggunakan penelitian kualitatif. Sumber data pada penelitian ini menggunakan novel Puspita Rinengga. Data penelitian ini menggunakan kata, kalimat, percakapan yang berkaitan dengan tindakan menyimpang dan tindakan kekerasan. Teknik mengumpulkan data dalam penelitian ini menggunakan teknik pustaka, teknik membaca, teknik mencatat, dan teknik mengelompokkan data. Teknik analisis data dalam penelitian ini dibagi menjadi 4 yaitu persiapan dan pengorganisasian data, reduksi data, menyajikan data dan kesimpulan. Hasil dan pembahasan dari penelitian ini adalah (1) tindakan menyimpang wujudnya adalah biseksual, menjadi banci dan PSK (2) tindakan kekerasan yang wujudnya adalah ditelantarkan dan dilarang mandiri yang menyebabkan kesengsaraan dan ketergantungan ekonomi Kata Kunci: Tindakan menyimpang, Ditelantarkan, Dilarang Mandiri